MIKROMORFOLOGI ALAT KELAMIN PRIMER BIAWAK AIR (Varanus salvator bivittatus) JANTAN (Micromorphological Structure of Primary Reproductive Organ of Male Water Monitor Lizard (Varanus salvator bivittatus)) - M, Mahfud; Winarto, Adi; Nisa, Chairun (Jurnal Kedokteran Hewan, 2016)
The study aims to determine the histological structure of the testes, ductus epididymidis and ductus deferens of Varanus salvator bivittatus. The tissue samples were obtained by the histological techniques preparation with thickness section is 3-4 m then stained using hematoxylin-eosin (HE) and Masson's Trichrome (MT). The result showed that testes are covered by tunica vaginalis and tunica albuginea (tunica fibrous and tunica vasculosa). Tubulus seminiferous as a parenchyma are found in lobules of testes which are formed by septum as extension of tunica albuginea. Tubulus seminiferous is composed by layers of germinal epithelium cells consist of spermatogenia, Sertoli cell, spermatocyte and spermatid which is developed further to be spermatozoa in the lumen of tubulus. Among the tubulus seminiferous, there are groups of epithelioid cells called Leydig cells. The end of tubulus seminiferous formed ductus epididymidis which then ended up and known as ductus deferens. Epididymis is covered by dense connective tissue. Ductus epididymidis is divided into three segments: cranial, medial and caudal. It is lined by pseudostratified columnar epithelium which is varied in its thickness, amount and diameter of lumen. Lumen of the ductus deferens was lined by pseudostratified ciliated columnar epithelium and thin muscularis mucosal layer and thick circular smooth muscle were covered externally.Key words: Varanus salvator bivittatus, testes, ductus epididymidis, ductus deferens, micromorphology